Studying respiratory rhythm generation in a developing bird: hatching a new experimental model using the classic in vitro brainstem-spinal cord preparatio - Vincen-Brown, Michael A. (Respir Physiol Neurobiol, 2015)
It has been more than thirty years since the in vitro brainstem-spinal cord preparation was first presented as a method to study automatic breathing behaviors in the neonatal rat. This straightforward preparation has led to an incredible burst of information about the location and coordination of several spontaneously active microcircuits that form the ventrolateral respiratory network of the brainstem. Despite these advances, our knowledge of the mechanisms that regulate central breathing behaviors is still incomplete. Investigations into the nature of spontaneous breathing rhythmicity have almost exclusively focused on mammals, and there is a need for comparative experimental models to evaluate several unresolved issues from a different perspective. With this in mind, we sought to develop a new avian in vitro model with the long term goal to better understand questions associated with the ontogeny of respiratory rhythm generation, neuroplasticity, and whether multiple, independent oscillators drive the major phases of breathing. The fact that birds develop in ovo provides unparalleled access to central neuronal networks throughout the prenatal period—from embryo to hatchling—that are free from confounding interactions with mother. Previous studies using in vitro avian models have been strictly limited to the early embryonic period. Consequently, the details and even the presence of brainstem derived breathing-related rhythmogenesis in birds have never been described. In the present study, we used the altricial zebra finch (Taeniopygia guttata) and show robust spontaneous motor outflow through cranial motor nerve IX, which is first detectable on embryonic day four and continues through prenatal and early postnatal development without interruption. We also show that brainstem oscillations change dramatically over the course of prenatal development, sometimes within hours, which suggests rapid maturational modifications in growth and connectivity. We propose that this experimental preparation will be useful for a variety of studies aimed at testing the biophysical and synaptic properties of neurons that participate in the unique spatiotemporal patterns of avian breathing behaviors, especially in the context of early development.